Increased Blood Pressure Dipping in Restless Legs Syndrome With Rotigotine: A Randomized Trial. Issue 12 (2nd September 2020) - Chenini, Sofiene; Rassu, Anna Laura; Barateau, Lucie; Lopez, Regis; Carlander, Bertrand; Guiraud, Lily; Jaussent, Isabelle; Dauvilliers, Yves
Abstract: Objective: The objective of this study was to assess the rotigotine effect on the nocturnal blood pressure (BP) dip by 24‐hour ambulatory BP monitoring and on endothelial function in patients with restless legs syndrome (RLS) compared with placebo. Methods: In this double‐blind, placebo‐controlled trial, 76 adult patients with moderate to severe RLS and periodic legs movements in sleep index ≥10/hour were randomized to rotigotine at optimal dose of 3 mg per day or placebo for 6 weeks. A total of 6 patients had a major protocol deviation. Polysomnography, ambulatory BP monitoring, and endothelial function were assessed at baseline and end point. The primary outcome was the between‐group difference in the percentage of BP nondipper profiles at end point. The main secondary outcomes were the mean BP dip, periodic legs movements in sleep index, and endothelial function. Results: Of the 70 patients (age, 59.4 ± 11.40; 43 women) randomized to rotigotine (n = 34) and placebo (n = 36), 66 (33 rotigotine, 33 placebo) completed the study. The percentage of BP nondippers at end point was higher in the placebo than in the rotigotine group (systolic BP, 72.22% vs 47.06%; diastolic BP, 47.22% vs 20.59%; P < 0.05). Mean BP dip at end point was higher in the rotigotine than in the placebo group (systolic BP, 11.24 ± 6.15 vs 6.12 ± 7.98; diastolic BP, 15.12 ± 7.09 vs 9.36 ± 10.23; P < 0.05). Endothelial function was comparable between the groups. No significant safety concerns were reported with similar incidences of adverse events between groups. Conclusion: Rotigotine increased the percentage of BP dipper profiles and the BP dip in patients with RLS. Future studies should assess whether this change is associated with a reduction in the long‐term cardiovascular risk in RLS. © 2020 International Parkinson and Movement Disorder Society